Neutrino energy loss by electron capture in magnetic field at the crusts of neutron stars - 刘晶晶 罗志全 (Chinese physics C, 2008)
Based on the p-f shell model, the effect of strong magnetic field on neutrino energy loss rates by electron capture is investigated. The calculations show that the magnetic field has only a slight effect on the neutrino energy loss rates in the range of 10^8-10^13 G on the surfaces of most neutron stars. But for some magnetars, the range of the magnetic field is 10^13-10^18 G, and the neutrino energy loss rates are greatly reduced, even by more than four orders of magnitude due to the strong magnetic field.